Demarcation of Topologically Associating Domains Is Uncoupled from Enriched CTCF Binding in Developing Zebrafish - Pérez-Rico, Yuvia A. (iScience, 2020)
CCCTC-binding factor (CTCF) is a conserved architectural protein that plays crucial roles in gene regulation and three-dimensional (3D) chromatin organization. To better understand mechanisms and evolution of vertebrate genome organization, we analyzed genome occupancy of CTCF in zebrafish utilizing an endogenously epitope-tagged CTCF knock-in allele. Zebrafish CTCF shares similar facets with its mammalian counterparts, including binding to enhancers, active promoters and repeat elements, and bipartite sequence motifs of its binding sites. However, we found that in vivo CTCF binding is not enriched at boundaries of topologically associating domains (TADs) in developing zebrafish, whereas TAD demarcation by chromatin marks did not differ from mammals. Our data suggest that general mechanisms underlying 3D chromatin organization, and in particular the involvement of CTCF in this process, differ between distant vertebrate species.